Integracja wiedzy o myśleniu i mózgu - Tempczyk, Michał (Filozofia Nauki, 1994)
This article is a polemic with the thesis held by J. Bobryk that we will never succeed in giving a unified description of human thinking and physiological processes taking place in human brain. The author rejects this view on the basis of the results achieved by modelling the brain's activities with the help of the theory of chaos. These models treat the brain as an incredibly complex dynamical system in which the order apprears as a result of mutual interactions of big neuron collections. The significant empirical material was gathered, ilustrating chaotic dynamics of the sense of sight, muscles movements, concentration etc. There seems to be no unsurmountable obstacles on the way of creating the unified theory of the brain dynamics and the consciousness.